Prognosis of Elderly Japanese Patients Aged ≥80 Years Undergoing Hemodialysis - Shingo Hatakeyama; Hiromi Murasawa; Itsuto Hamano; Ayumu Kusaka; Takuma Narita; Masaaki Oikawa; Daisuke Noro; Kazuhisa Hagiwara; Hirofumi Ishimura; Takahiro Yoneyama; Yasuhiro Hashimoto; Takuya Koie; et al. (The Scientific World Journal)
Although the number of elderly patients requiring dialysis has increased, data regarding the prognosis of elderly patients undergoing hemodialysis are limited. In the present study, prognosis in Japanese hemodialysis patients aged ≥80 years was evaluated. From January 1988 to July 2013, 1144 consecutive patients with end-stage renal disease required renal replacement therapy at our institution; of these, 141 were aged ≥80 years. These patients’ charts were retrospectively reviewed for relevant clinical variables and survival time. The life expectancies table from the National Vital Statistics database was used, and prognostic factors were assessed by multivariate analysis. In total, 107 deaths (76%) were recorded during the study period. The median survival time and estimated life-shortening period in the patients were 2.6 years and −5.3 years, respectively. Eastern Cooperative Oncology Group Performance Status and hemoglobin level were revealed as prognostic factors in the multivariate analysis. Estimates of prognosis and prognostic factors may provide useful information for physicians as well as elderly patients with end-stage kidney disease.